2022
DOI: 10.3389/fchem.2022.958561
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29b/graphene oxide–polyethyleneglycol–polyethylenimine complex incorporated within chitosan hydrogel promotes osteogenesis

Abstract: MicroRNAs (miRNAs) play a pivotal role in regulating a number of physiologic and pathologic processes including bone marrow mesenchymal stem cell (BMSC) osteogenic differentiation, making them a candidate used to promote osteogenesis. However, due to intrinsic structure and characteristics, “naked” miRNAs are unstable in serum and could not pass across the cellular membrane. Nano delivery systems seem to be a solution to these issues. Recently, graphene oxide (GO)-based nanomaterials are considered to be promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…MiR-365a-3p has been reported as substantially downregulated in breast, gastric, and HCC cancers [ 33 , 34 ]. Delivering naked miRNA to target tissue is difficult due to endosomal entrapment, enzymatic degradation in body fluids, and immune surveillance [ [35] , [36] , [37] , [38] , [39] , [40] ]. Therefore, using proper carriers can enhance the stability, permeability, and efficiency of tumor suppressor microRNA transfection.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-365a-3p has been reported as substantially downregulated in breast, gastric, and HCC cancers [ 33 , 34 ]. Delivering naked miRNA to target tissue is difficult due to endosomal entrapment, enzymatic degradation in body fluids, and immune surveillance [ [35] , [36] , [37] , [38] , [39] , [40] ]. Therefore, using proper carriers can enhance the stability, permeability, and efficiency of tumor suppressor microRNA transfection.…”
Section: Discussionmentioning
confidence: 99%
“…RNA loading into nanomaterials combined with hydrogels can improve the retention time around tumors and the uptake of RNA into cancer cells [ 173 ]. Qin et al [ 174 ] prepared miR-29b/GO-PEG-PEI@chitosan hydrogel that shows excellent miR-29b loading capacity and delivery efficiency. In vivo experiments showed that transfection of BMSCs significantly promoted their osteogenic differentiation and did not trigger inflammatory responses.…”
Section: Hydrogel Designs To Enable Therapeutic Gene Releasementioning
confidence: 99%
“…Research into novel methods for inducing bone regeneration has been prompted by the limited application of growth factors due to their short half-life, low bioactivity, and high production costs of recombinant proteins. , Nucleic acid provides an up-and-coming alternative for delivering the growth factors, including DNA , and RNA. , At the transcriptional and post-transcriptional levels, they can induce changes in gene expression. The cationic liposomes are the most common delivery systems for a nucleic acid.…”
Section: Application Of Photoresponsive Hydrogels In Bone Tissue Engi...mentioning
confidence: 99%
“…168,169 Nucleic acid provides an up-and-coming alternative for delivering the growth factors, including DNA 170,171 and RNA. 172,173 At the transcriptional and posttranscriptional levels, they can induce changes in gene expression. The cationic liposomes are the most common delivery systems for a nucleic acid.…”
Section: Application Of Photoresponsive Hydrogels In Bone Tissue Engi...mentioning
confidence: 99%